Metode Index Card Match Terhadap Peningkatan Hasil Belajar Peserta Didik Pada Mata Pelajaran Al-Qur’an Hadits Di Madrasah Ibtidaiyah - Waode Yani (Diniyah: Jurnal Pendidikan Dasar, 2021)
This study aims to improve learning outcomes of Al-Qur'an Hadith for students at MI Wandoka through the application of the Index Card Match learning model. This research employs classroom action research (CAR), which is carried out in 2 cycles, for fourth grade students in the even semester of the 2019/2020 school year. The instruments used are documentation, learning outcomes tests, teacher and student observation sheets. The research procedure consists of planning, implementing actions, observing, evaluating and reflecting. The results showed that the application of the Index Card Match learning model could improve student learning outcomes at MI Wandoka. The average score of students in the pre-cycle reached 59.14 with a learning completeness of 23.80%. After the first cycle of action, learning completeness reached 52.38% with an average value of 63.80. Then in the second cycle, learning completeness reached 80.95% with an average value of 71.90.Keywords: Index card match learning model, learning outcomes of Al-Qur'an Hadith, elementary school